(untitled) (Texas Journal of Engineering and Technology, 2022)
The 21st century is characterized by different trends, including advanced digital technologies and services. These technologies comprise advanced telecommunication systems that enhance communication between different parties thus, ease of information awareness between people in different locations. For this reason, telecommunication systems have been used by government agencies and NGOs to help promote the practice of democracy and respect for human rights. Countries such as Iraq have been identified as entities that use telecommunication systems to positively and negatively encourage the practice of human rights and democracy. This study aims to discuss the suitability of telecommunication systems in the practice of democracy and human rights in Iraq. The paper has used the case study data collection method to acquire an in-depth and multi-faceted understanding of the complex issue in its reallife context. The results show that telecommunications have been used often to ensure democracy and human rights are effectively practised. The paper’s results comprise 4 case studies that show the positive use of telecommunication systems in the practice of human rights and democracy within a given country. In contrast, two case studies show examples of negative use of telecommunication systems based on retaining control or governmental power. Lastly, one case study shows how telecommunication systems can be important in regions where governance, democracy and human rights are not intact. The study’s findings show that telecommunication systems benefit governments and citizens by ensuring that democracy and human rights are practised appropriately.